Language Style in Song Lyrics of â€œDoa Sepasang Petani Mudaâ€, â€œNyanyian Burung Pepohonan,â€ â€œBahasa Matahari,â€ and â€œSenandung Pucuk-Pucuk Pinusâ€ by Ebiet G. Ade - Astuti, Sri Puji; Bunga, Aramuti (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS, 2023)
The purpose of this research is to unveil the stylistic elements based on sentence structure in the lyrics of "Doa Sepasang Petani Muda," "Nyanyian Burung dan Pepohonan," "Bahasa Matahari," and "Senandung Pucuk- Pucuk Pinus" by Ebiet G. Ade, and to determine the stylistic elements based on whether or not the meaning is direct in these four song lyrics. Data for this study was collected using the observational method by observing and listening to the songs available on YouTube. Data consists of excerpts from the lyrics of these songs that contain figurative language used in the lyrics. Subsequently, this data is classified based on the types of figurative language used. Statistical theory is employed for data analysis. The research findings reveal that the stylistic elements based on sentence structure found in the lyrics of "Doa Sepasang Petani Muda," "Nyanyian Burung dan Pepohonan," "Bahasa Matahari," and "Senandung Pucuk-Pucuk Pinus" by Ebiet G. Ade include the stylistic elements of parallelism and repetition. Regarding the directness of meaning, the four song lyrics make use of figures of speech such as personification, irony, pleonasm, and rhetoric in their lyrics.Â